An Image-based Search for Pulsar Candidates in the MeerKAT Bulge Survey - Dale A. Frail; Emil Polisensky; Scott D. Hyman; William D. Cotton; Namir E. Kassim; Michele L. Silverstein; Rahul Sengar; David L. Kaplan; Francesca Calore; Joanna Berteaud; Maïca Clavel; Marisa Geyer; et al. (The Astrophysical Journal)
We report on the results of an image-based search for pulsar candidates toward the Galactic bulge. We used mosaic images from the MeerKAT radio telescope that were taken as part of a 173 deg ^2 survey of the bulge and Galactic center of our Galaxy at L band (856–1712 MHz) in all four Stokes I , Q , U , and V . The image rms noise levels of 12–17 μ Jy ba ^−1 represent a significant increase in sensitivity over past image-based pulsar searches. Our primary search criterion was circular polarization, but we used other criteria, including linear polarization, in-band spectral index, compactness, variability, and multiwavelength counterparts to select pulsar candidates. We first demonstrate the efficacy of this technique by searching for polarized emission from known pulsars and comparing our results with measurements from the literature. Our search resulted in a sample of 75 polarized sources. Bright stars or young stellar objects were associated with 28 of these sources, including a small sample of highly polarized dwarf stars with pulsar-like steep spectra. Comparing the properties of this sample with the known pulsars, we identified 30 compelling candidates for pulsation follow-up, including two sources with both strong circular and linear polarization. The remaining 17 sources are either pulsars or stars, but we cannot rule out an extragalactic origin or image artifacts among the brighter, flat-spectrum objects.